Dynamic thermal environment and thermal comfort. (3rd September 2015) - Zhu, Y.; Ouyang, Q.; Cao, B.; Zhou, X.; Yu, J.
Abstract: Research has shown that a stable thermal environment with tight temperature control cannot bring occupants more thermal comfort. Instead, such an environment will incur higher energy costs and produce greater CO2 emissions. Furthermore, this may lead to the degeneration of occupants' inherent ability to combat thermal stress, thereby weakening thermal adaptability. Measured data from many field investigations have shown that the human body has a higher acceptance to the thermal environment in free‐running buildings than to that in air‐conditioned buildings with similar average parameters. In naturally ventilated environments, occupants have reported superior thermal comfort votes and much greater thermal comfort temperature ranges compared to air‐conditioned environments. This phenomenon is an integral part of the adaptive thermal comfort model. In addition, climate chamber experiments have proven that people prefer natural wind to mechanical wind in warm conditions; in other words, dynamic airflow can provide a superior cooling effect. However, these findings also indicate that significant questions related to thermal comfort remain unanswered. For example, what is the cause of these phenomena? How we can build a comfortable and healthy indoor environment for human beings? This article summarizes a series of research achievements in recent decades, tries to address some of these unanswered questions, and attempts to summarize certain problems for future research.